Effect of alcohol on blood pressure, cholesterol and certain electrolytes concentration - Mahmud Jubouri (College of Education for Pure Sciences, 2012)
Abstract This study was conducted to determine the effect of alcohol on human health through measurement of some changes in physiology, biochemical and electrolytes in serum blood of alcohol addicts persons and these change include (blood pressure, cholesterol concentration, total & direct, conjection bilirubin, sodium concentration, potassium, calcium and chloride) for forty blood samples from normal and alcohol addicted healthy males then they compared with (20) blood samples of a non-alcoholic healthy persons as a control group. Results showed increase in the percentage of these changes in serum blood of those persons account quantity of drink, attain increase percent in concentration of sodium (104.39, 104.02, 104.61 %) account quantity of drink (250, 500, 1000) but attain percent increase concentration of chloride (106.52،106.90, 101.82 %), but the increase percent in concentration of cholesterol (101.71, 101.14,100.9 %) while attain most those persons percent increase in blood pressure attain (63%).